Shared rare genetic variants in multiplex autism families suggest a social memory gene under selection - Kang Seon Lee; Taeyeop Lee; Mujun Kim; Elizaveta Ignatova; Hyo-Jeong Ban; Min Kyung Sung; Younghoon Kim; Youn-Jae Kim; Jin-Hee Han; Jung Kyoon Choi (Scientific Reports)
Abstract Autism spectrum disorder (ASD) affects up to 1 in 59 children, and is one of the most common neurodevelopmental disorders. Recent genomic studies have highlighted the role of rare variants in ASD. This study aimed to identify genes affected by rare variants shared by siblings with ASD and validate the function of a candidate gene FRRS1L. By integrating the whole genome sequencing data of 866 multiplex families from the Hartwell Foundation’s Autism Research and Technology Initiative and Autism Speaks MSSNG project, we identified rare variants shared by two or more siblings with ASD. Using shared rare variants (SRVs), we selected candidate genes for ASD. Gene prioritization by evolutionary features and expression alterations on autism identified FRRS1L in two families, including one with impaired social behaviors. One variant in this family was 6 bp away from human-specific trinucleotide fixation. Additionally, CRISPR/Cas9 experiments demonstrated downregulation by a family variant and upregulation by a fixed site. Population genetics further demonstrated that upregulation of this gene has been favored during human evolution. Various mouse behavioral tests showed that Frrs1l knockout specifically impairs social novelty recognition without altering other behavioral phenotypes. Furthermore, we constructed humanized mice by introducing human sequences into a mouse genome. These knockin mice showed improved abilities to retain social memory over time. The results of our population genetic and evolutionary analyses, behavior experiments, and genome editing propose a molecular mechanism that may confer a selective advantage through social memory enhancement and may cause autism-related social impairment when disrupted in humans. These findings highlight the role of FRRS1L, the AMPA receptor subunit, in social behavior and evolution.